2017
DOI: 10.1213/ane.0000000000001926
|View full text |Cite
|
Sign up to set email alerts
|

Massive Transfusion in Cardiac Surgery: The Impact of Blood Component Ratios on Clinical Outcomes and Survival

Abstract: Background Cardiac surgery is the most common setting for massive transfusion in medically advanced countries. Studies of massive transfusion following injury suggest that the ratios of administered plasma and platelets (PLT) to red blood cells (RBCs) affect mortality. The Red Cell Storage Duration Study (RECESS) was a large randomized trial of the effect of RBC storage duration in patients undergoing complex cardiac surgery. Data from that study was analyzed retrospectively to investigate the association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…In the present study, MRT was defined as receiving at least 4 units of RBCs during hospitalization. The minimum number of RBCs in MRT has been variously set at 4, [3] 5, [17] 6, [9] or 8, [28] and we opted for 4 as our cut-off because morbidity sharply increases beyond this level, [8] and postoperative complications even increase 19.4% ( P < .01) when the patients receive ≥4 units of RBCs. [29]…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, MRT was defined as receiving at least 4 units of RBCs during hospitalization. The minimum number of RBCs in MRT has been variously set at 4, [3] 5, [17] 6, [9] or 8, [28] and we opted for 4 as our cut-off because morbidity sharply increases beyond this level, [8] and postoperative complications even increase 19.4% ( P < .01) when the patients receive ≥4 units of RBCs. [29]…”
Section: Discussionmentioning
confidence: 99%
“…Между группами с использованием крови и отказом от нее выявлены значимые различия в уровне гемоглобина и гематокрита, однако с учетом анализа интраоперационного периода (уровня лактата крови, сатурации венозной крови, пульсоксиметрии и церебральной оксиметрии) гемической гипоксии и нарушения доставки кислорода к головному мозгу не обнаружено. Вместе с тем уровень маркеров СВО оказался ниже в группе больных без трансфузии, что согласуется с теорией о компонентах донорской крови как одном из источников развития СВО [4]. Логичным продолжением данного предположения должен быть более низкий уровень повреждения нейроваскулярной единицы в контрольной группе, что и подтвердилось с помощью маркеров.…”
Section: Discussionunclassified
“…Причина данной проблемы в повышенной кровопотере в интра-и послеоперационном периоде кардиохирургических операций и специфической для детей особенности -добавлении компонентов донорской крови в объем первичного заполнения аппарата ИК как метода профилактики критической гемодилюции. Однако в литературе представлены исследования, доказывающие роль интраоперационной трансфузии в развитии СВО [4]. В свою очередь, в головном мозге СВО реализуется с вовлечением нейроваскулярной единицы, последующим нейровоспалением и нарушением функции и структуры нейронов и гематоэнцефалического барьера [5].…”
Section: Introductionunclassified
“…Of note, it has been shown that massive hemorrhage is likely to be associated with huge trauma, abnormal anatomy, or operation techniques, which will lead to poor prognosis of cardiac surgery ( 15 , 16 ). Therefore, these kinds of patients were excluded from our research to offset bias.…”
Section: Methodsmentioning
confidence: 99%